Pengaruh Penerapan Syariat Islam Sebagai Preferensi Orang Tua di Kabupaten Aceh Tengah dalam Memilih Lembaga Pendidikan Formal (Study Deskriptif Komparatif: Sekolah Umum, Madrasah dan Pesantren) - Daulay, Leni Agustina; Fitri, Aida (BELAJEA: Jurnal Pendidikan Islam, 2019)
This research aims to know the influence of the application of the Shariah as the preferences of older people in Central Aceh in choosing formal education instutions. This research is quantitative descriptive research. The results of this research show that the factor knowledge of parents reagarding Islamic Jurisrudence and its application as well as economic, educational background of parents dealing with the positive decision of the parents send the children in public school, boarding schools and madrasah in Central Aceh. The next factor is the parents knowledge about Islamic Jurisrudence and its application as well as economic, educational background of parents can explain its effect on the dependent variable i.e. decisions parents send children in public school, boarding schools and madrasah. Based on the test silmutaneously demonstrated knowledge factors parents regarding Islamic Jurisrudence and its application as well as educational background, economically significant influential parents against decisions parents send children in public school, boarding schools and madrasah in Central Aceh. Then test the partial basis for each variable that is knowledge og the elderly on Islamic Jurisrudence and its application as well as educational background, economically significant influential parents against decisions parents send children at public school, boarding schools and madrasah in Central Aceh.